Polar Thermospheric Winds and Temperature Observed by Fabry‐Perot Interferometer at Jang Bogo Station, Antarctica. Issue 9 (27th September 2017) - Lee, Changsup; Jee, Geonhwa; Wu, Qian; Shim, Ja Soon; Murphy, Damian; Song, In‐Sun; Kwon, Hyuck‐Jin; Kim, Jeong‐Han; Kim, Yong Ha
Abstract: Upper atmospheric neutral winds and temperature have been observed by the Fabry‐Perot interferometer (FPI) which was installed at Jang Bogo Station (JBS), Antarctica, in 2014. Since JBS is mostly located within the polar cap region, the observed thermospheric winds at 250 km show strong diurnal variations with notable antisunward motions due to the effects of plasma convection. The winds at 87 km, on the other hand, show semidiurnal variations due to the lower atmospheric tidal effects. We found that the winds from green line emission show largely diurnal variations, unlike the other independent observations, which might be due to the auroral contamination. The horizontal wind model 2014 winds at 250 km show reasonable agreement with FPI winds, while large discrepancies exist at 87 km in terms of seasonal variations. There is a distinctive asymmetric seasonal variation of the thermospheric zonal wind in the dusk and dawn sectors. FPI temperatures at 250 km show a fairly close correlation with Kp index, especially in 2015 when the geomagnetic activity is stronger. However, the temperatures at 87 km are mostly independent on Kp index. Finally, during the intense geomagnetic storm, thermospheric winds and temperature are significantly disturbed and Thermosphere Ionosphere Electrodynamics General Circulation Model simulations are in surprisingly good agreement with observation for winds but the temperatures are significantly underestimated during the whole storm period. Key Points: New FPI observation for the polar upper atmospheric winds and temperature is initiated at Korean Antarctic station in 2014 HWM14 and TIEGCM are evaluated for polar cap region by comparing FPI wind measurements The effects of intense geomagnetic storm on 17 March 2015 on thermospheric wind and temperature are investigated in the polar cap region